2023
DOI: 10.1037/cps0000178
|View full text |Cite
|
Sign up to set email alerts
|

A social identity approach to facilitating therapy groups.

Alysia M. Robertson,
Tegan Cruwys,
Mark Stevens
et al.

Abstract: Group therapy offers both an effective and cost-effective means to support mental health. Facilitators are key to the benefits that clients derive from group therapy. However, minimal research has examined how their effectiveness can be maximized. To address this limitation, we propose that group facilitators should be conceptualized as leaders, and that identity leadership theory provides a valuable framework for efforts to understand and increase their effectiveness. We introduce and review identity leadersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 151 publications
0
1
0
Order By: Relevance
“…Numerous studies have provided evidence for wide-ranging benefits of leaders adhering to these four principles. For example, researchers have found that identity leadership can help mobilise political support [ 124 , 125 ], increase organisational performance [ 126 ] and lay a foundation for group therapy patients to experience better therapeutic outcomes [ 127 , 128 ]. Most relevant in the present context, researchers have also found evidence that identity leadership can help buffer against poor mental health.…”
Section: A Social Identity Approach To Athlete Mental Healthmentioning
confidence: 99%
“…Numerous studies have provided evidence for wide-ranging benefits of leaders adhering to these four principles. For example, researchers have found that identity leadership can help mobilise political support [ 124 , 125 ], increase organisational performance [ 126 ] and lay a foundation for group therapy patients to experience better therapeutic outcomes [ 127 , 128 ]. Most relevant in the present context, researchers have also found evidence that identity leadership can help buffer against poor mental health.…”
Section: A Social Identity Approach To Athlete Mental Healthmentioning
confidence: 99%